Empowering dried bamboo shoot MSMEs through product design and digital promotion - Heni Ermewaningsih; Fransiska Elly Renni Susanti; Anisa Safitri (University of Merdeka Malang, 2026)
This community service program aimed to enhance the capacity of dried bamboo shoot micro, small, and medium enterprises (MSMEs) through product packaging development and digital promotion assistance. The program was conducted in Bokak Sebumbun Village, Sekadau Hilir District, Sekadau Regency, involving 12 MSME participants. The main challenges faced by the participants included the use of simple packaging without product identity and the limited utilization of digital media for product promotion. The program was implemented through a needs assessment, product packaging design training, and hands-on assistance in using WhatsApp Business with participants’ own smartphones. The results showed that participants successfully developed more informative product packaging by adding product labels, created digital product catalogs, promoted products through digital media, and utilized WhatsApp Business as a communication platform with customers. Evaluation results indicated an increase in the number of participants using WhatsApp Business for product promotion from 2 to 10 participants. In addition, the average pre-test score increased from 1.8 to 4.2 after the training and mentoring activities. The program contributed positively to improving participants' knowledge and practical skills in product packaging development and digital promotion, thereby supporting the marketing capacity and competitiveness of dried bamboo shoot MSMEs.